Amores públicos e vidas privadas: um estudo sobre a mulher no casamento em Fogo Morto e São Bernardo - Pessoa, Francielly Alves (2015)
Our research focus two Brazilian novels – Fogo Morto, by José Lins do Rego, and São Bernardo, by Graciliano Ramos, published respectively in 1943 and 1934. We point out, on these two narratives, the female characters Amelia and Madalena, in order to analyze their behavior as married subjects inside a very traditional social system in the countryside of the Northeast of Brazil at that time. In order to read critically how these women are constructed by the authors and the narrators in these narratives, as well as the role they play in the social system they are inserted, where the feminine tend to be silenced or made invisible, we discuss concepts about public and private spheres, with a special interest in the way in which cultural and gender studies has been leading such spheres of social life. With the reading and selection of a theoretical framework which brings important contribution to our analysis of the literary texts, we take studies by Lauretis (1994) in respect to gender technologies, Perrot (2003) about the theory of silencing and gender, Okin (2007) to discuss about the relation between gender and politics, and to discuss resistance of the dominant models we take Bourdieu (2014) studies. We highlight the almost total separation observed between the world of women and men in the novels analyzed. Finally, we point out some ways through which both female characters succeed, even in a non-explicit way, in interfering in the social system they are inserted and in the way their love relationships develop through the union (not always a loving one) they establish with their husbands. Thus, we discuss the context of these two novels within a wider, historical and social context, in other words, considering how the relationships between men and woman were established in Brazilian society in the thirties and forties.